What keeps leaders up at night : recognizing and resolving your most troubling management issues - Lipkin, Nicole A. (AMACOM, 2013)
"No matter how many initiatives you spearhead or how hard you think about decisions, you will make the occasional management misstep. All leaders do. You can lie awake at night questioning yourself or you can read this book. The book examines engagement, motivation, expectation, emotions, interpersonal and group dynamics--all the psychological principles that play pivotal roles in the workplace. Featuring illuminating examples and exercises, What Keeps Leaders Up at Night shines a bright light into the dark corners where all leaders struggle with their own shortcomings."--Jacket.